Extraction and preliminary chemical characterization of the venom of the spider wasp Pepsis decorata (Hymenoptera: Pompilidae). (August 2018) - Nolasco, Matheus; Biondi, Ilka; Pimenta, Daniel C.; Branco, Alexsandro
Abstract: Arthropod venoms may be considered important sources of bioactive molecules; however, technical difficulties, such as venom extraction and homogeneity may impair the biochemical identification of new molecules. In this context, we have developed a method to maintain wasps in captivity that allows the collection of the venom, without use of chemical, mechanical or electrical stimuli. The crude venom was analyzed by RP-HPLC-ESIQ-ToF and 20 peptides were identified by de novo peptide sequencing, among them Eumenine-Mastoparan and a Ponericin-G2-simile peptide. Highlights: Fast and efficient method of extraction pure venom from pompilids. Milking method not fatal to the wasp, even repeated several times. Wasps in captivity plus this form of extraction allows accumulation of large amounts of venom.